FSKTM E-Community System / Lung Hung Ping - Lung , Hung Ping (2005)
By the middle of 1990, World Wide Web had transformed the online world tremendously. Users from all over world were able to access and select various type of information from the online world through the system at hypertext called homepage. FSKTM E-Community is a web based system that allows the user to discuss and share any issues or problems in this place. The modules that included in this system are notice board, widen knowledge, complaint, forum and FAQs. Which this module will be able to add, edit, view, delete and reply by the user. The development process of FSKTM E- Community system involves several stages, which include literature review, system analysis and requirement and system design. The reports will also cover the process models, the research plan and methodologies, the analysis an existing system and the design of the new system. The waterfall model with prototyping approach was selected for the development process for the strengths and reduces the risk involved system will ASP.Net as dynamic web tool, HS for web server and Microsoft SQL for its database implementation.